Long-Term Impact of War, Civil War, and Persecution in Civilian Populations—Conflict and Post-Traumatic Stress in African Communities - Musisi, Seggane; Kinyanda, Eugene (Frontiers in Psychiatry, 2020)
This chapter describes how chronic conflict, warfare, and persecution, as lived experiences, have created significant mental distress in communities on the African continent. There is a growing body of research that highlights increasing mental distress in Africa e.g., about sexuality, health, disease, modernity, climate, politics, culture, religion, ethnicities, race, economies etc. Many of these stresses and uncertainties are driven by political persecution, war, and conflict. This has shaped many African people’s attitudes and government policies and an increasing scholarly interest in exploring these “uncertainties and mental distresses in Africa.” The chapter will show how trauma, as seen in conflict/post-conflict settings in Africa, causes significant mental stress and associated social problems as well as medically-defined PTSD syndromes, anxiety, and depression which cause much morbidity and retard development in many African communities. Taking a classical look at post-traumatic stress disorder, PTSD, the chapter explores the presentation of the various physical and mental clinical syndromes related to war-trauma on the African continent and the consequent health-seeking behaviors of the African peoples in this regard. The term “culture-bound PTSD syndromes” will be introduced and discussed in the broader context of treatment, rehabilitation, and prevention on the continent and worldwide. It will also discuss the dilemma of the vicious cycles of trauma driven by appetitive aggression in today’s Africa which portends to further retard socio-economic development and drives the trans-generational perpetuation of ethnic-based conflicts including genocides. Despite this mass traumatization, the chapter points to the virtual absence of post-conflict mental health policies in almost all African countries, hence leading to discussions of “best-practices” recommendations.